2011
DOI: 10.1017/s0007114511004144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with unprocessed and ethanol-extracted apple pomaces on caecal fermentation, antioxidant and blood biomarkers in rats

Abstract: The present 4-week study on growing Wistar rats was aimed at assessing the potential advantages of dietary supplementation with apple pomace containing both fibre and polyphenols, which enables nutritional exploitation of the physiological traits of both compounds. A total of twenty-four rats, assigned to the control (C), group fed with a diet supplemented with 14 % of processed apple pomace (A) and group fed with a diet supplemented with 15 % unprocessed apple pomace (AP) groups, were fed the following iso-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Previous studies conducted in our laboratory as well as those by other researchers revealed that inclusion of dietary fructans, apple pomace and polyphenolic fraction from chicory and apple significantly decreased activity of β-glucuronidase released from bacterial cells into the large gut environment (Bouhnik et al, 2007;Juśkiewicz et al, 2011Juśkiewicz et al, , 2012. Among all experimental preparations, pectin was the only one associated with markedly increased activity of β-glucuronidase.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies conducted in our laboratory as well as those by other researchers revealed that inclusion of dietary fructans, apple pomace and polyphenolic fraction from chicory and apple significantly decreased activity of β-glucuronidase released from bacterial cells into the large gut environment (Bouhnik et al, 2007;Juśkiewicz et al, 2011Juśkiewicz et al, , 2012. Among all experimental preparations, pectin was the only one associated with markedly increased activity of β-glucuronidase.…”
Section: Discussionsupporting
confidence: 52%
“…After centrifugation at 4800 g for 5 min, the supernatant was collected and the residue was re-extracted twice with 3 ml of the same solvent to gain about 10 ml pooled extracts. The ethanolic extracts, containing most of the soluble polyphenols, were analysed by a Dionex HPLC coupled with a Gemini 5-mm C18 110A column (250 × 4.6 mm; Phenomenex Synergi; Torrance, CA; USA), as described previously by Juśkiewicz et al (2012).…”
Section: Chemical Analyses Of Plant Materials and Experimental Dietsmentioning
confidence: 99%
“…Ghibu et al [2013] have shown that a high-fructose diet (60% of the diet) can be used as a model to induce oxidative stress in rats. Also, Zagrodzki et al [2007] have shown that the diet high in fructose signifi cantly changes the antioxidant defence status of rats, which may be counteracted by the ad- Maffei et al [2007] have suggested that the consumption of whole apple provides a useful dietary source of active scavengers to protect cells and tissues from oxidative stress, whereas Juśkiewicz et al [2012] have demonstrated that the polyphenol-rich fi bre complexes from apple pomace exert positive effects on the antioxidant status of rats. In the present experiment, the parameters of antioxidant status did not change after AFP administration to a high-fructose diet.…”
Section: Discussionmentioning
confidence: 99%
“…were measured spectrophotometrically using the rate of -or o-nitrophenol release from the respective nitrophenyl-glycosides and expressed as μmol product formed per h per g of the digesta [Juśkiewicz et al, 2012].…”
Section: Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation